2022
DOI: 10.19088/basic.2022.018
|View full text |Cite
|
Sign up to set email alerts
|

What is Known About Capacity and Coordination of Social Assistance Programmes in Crisis Situations?

Rachel Slater,
Ella Haruna,
Daniela Baur

Abstract: This paper reviews the literature and documented evidence on capacity and coordination issues in crisis situations, where social protection and humanitarian assistance intersect. The paper finds that while there is a burgeoning literature that mentions capacity and coordination, very little of this focuses on crisis situations. Although both terms are mentioned frequently, they are rarely defined or robustly and systematically assessed. The little literature that does exist points to a substantial knowledge ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…At the heart of the Better Assistance in Crises (BASIC) Research agenda is an attempt to plug a knowledge gap about existing social protection programmes. Our inception phase scoping work demonstrated that, in the midst of massive interest in shock-responsive social protection (Longhurst and Slater 2022), little attention is paid to what happens to existing social protection in situations of protracted crisis (Slater, Haruna and Baur 2022;Slater 2022). By placing substantial emphasis on how to flex and expand programmes vertically and horizontally, the shock-responsive social protection agenda has tended to take attention away from if and how existing programmes are able to sustain delivery to existing beneficiaries in situations of climate and/or conflict crisis.…”
Section: Basic Research On Capacities To Sustain Existing Social Prot...mentioning
confidence: 99%
“…At the heart of the Better Assistance in Crises (BASIC) Research agenda is an attempt to plug a knowledge gap about existing social protection programmes. Our inception phase scoping work demonstrated that, in the midst of massive interest in shock-responsive social protection (Longhurst and Slater 2022), little attention is paid to what happens to existing social protection in situations of protracted crisis (Slater, Haruna and Baur 2022;Slater 2022). By placing substantial emphasis on how to flex and expand programmes vertically and horizontally, the shock-responsive social protection agenda has tended to take attention away from if and how existing programmes are able to sustain delivery to existing beneficiaries in situations of climate and/or conflict crisis.…”
Section: Basic Research On Capacities To Sustain Existing Social Prot...mentioning
confidence: 99%